CD4+ T Cells Play Distinct Roles during the Priming versus Effector Phases of Immune Checkpoint Therapy–Dependent Tumor Elimination by CD8+ T Cells - Samuel Ameh; Derek J. Theisen; Mahima Thapa; Jackson S. Turner; Abhinav Rangarajan; Christopher A. Nelson; Aaron J. Schmitz; Yuang Song; Ruan F. Vieira Medrano; Cora D. Arthur; J. Michael White; Kathleen C.F. Sheehan; et al. (Cancer Immunology Research, 2026)
Abstract It is well established that CD4+ T cells play a critical role in facilitating immune checkpoint therapy (ICT). Although CD4+ T-cell function in lymph nodes during CD8+ T-cell priming has been well investigated, their requirement at the effector phase in the tumor is only now beginning to be appreciated. Herein, we used our major histocompatibility complex class II–negative (MHC-II−) sarcoma models to confirm that CD4+ T cells are essential not only during T-cell priming but also to maintain T-cell effector function within the tumor. Depleting CD4+ T cells at the effector phase, after CD8+ T-cell priming had occurred, abolished ICT-induced tumor rejection despite the detection of tumor-specific CD8+ T cells and their intratumoral accumulation. CD4+ T cells were required for functional reinvigoration of CD8+ tumor-infiltrating lymphocytes by ICT, leading to enhanced cytokine production, expression of cytotoxicity, and reduced exhaustion—without affecting CD8+ T-cell proliferation. Mechanistically, CD4+ T-cell function at the effector phase did not require CD40/CD40L signaling, which is necessary for efficient priming but rather depended on IL2 and IFNγ. Using a T-cell receptor–mimic monoclonal antibody (1G10) specific for the dominant neoantigen:I-Ab complex on antigen-presenting cells formed during T3 sarcoma challenge, we further showed that ongoing MHC-II neoantigen presentation was necessary to sustain CD4+ T-cell help after priming. These findings reveal temporally distinct requirements for CD4+ T-cell help and establish a need for continuous CD4+/CD8+ T-cell cooperation as a prerequisite for anti–PD-1/anti–CTLA-4 ICT efficacy against MHC-II− tumors.